Exploring relevance, public perceptions, and business models for establishment of private well water quality monitoring service. (8th February 2019) - Thomson, Kalen K.; Rahman, Arifur; Cooper, Tom J.; Sarkar, Atanu
Summary: Existing public policies mostly focus on public water systems, leaving aside the quality issues regarding private wells in small and rural locations. Establishment of affordable and accessible water quality monitoring services may ensure acceptable levels of all the parameters. This paper aims to explore (a) health risk because of chemical contaminants of private wells, (b) population perspective on well water quality and monitoring, and (c) to create a business model of a centralized water quality monitoring service. The results show potential problems with toxic levels of arsenic, barium, cadmium, chromium, lead, mercury, and selenium. About 5% of the province's population is at risk for potential exposure to contaminated private well water. The survey reinforces that the successful implementation of water testing laboratories for private wells is a shared responsibility between well owners and the government organizations, and almost three‐fourths respondents were willing to share the cost up to certain limit. A business model including financial projections for a centralized water testing laboratory is presented. Drinking of unmonitored private well water is putting population health at risk. Either strong regulation with mandatory water testing or voluntary water testing with adequate government subsidy can ensure sustainable function of a centralized water testing laboratory.